Combination of ofatumumab and reduced-dose CHOP for diffuse large B-cell lymphomas in patients aged 80 years or older: an open-label, multicentre, single-arm, phase 2 trial from the LYSA group. Issue 1 (January 2017) - Peyrade, Frédéric; Bologna, Serge; Delwail, Vincent; Emile, Jean François; Pascal, Laurent; Fermé, Christophe; Schiano, Jean-Marc; Coiffier, Bertrand; Corront, Bernadette; Farhat, Hassan; Fruchart, Christophe; Ghesquieres, Herve; et al.
Summary: Background: In 2011 we reported a rituximab plus miniCHOP (reduced-dose cyclophosphamide, doxorubicin, vincristine, and prednisone) combination for patients older than 80 years with diffuse large B-cell lymphoma (DLBCL). The 2-year overall survival was 59% (95% CI 49–67) with an excess of early toxicity. To improve those results we tested the same chemotherapy protocol in combination with ofatumumab and a pre-phase treatment. Methods: For this open-label, multicentre, single-group, phase 2 trial, we recruited patients older than 80 years with untreated histologically-proven CD20-positive DLBCL, Ann Arbor stage I to IV, from 41 academic and hospital centres in France and Belgium. Patients received a pre-phase with oral vincristine (1 mg total dose 1 week before cycle 1 [day −7]) and oral prednisone (60 mg total dose starting 1 week before cycle 1, for 4 days [day −7 to day −4]) before the first cycle of the ofatumumab plus miniCHOP regimen. The regimen consisted of 1000 mg total dose of intravenous ofatumumab, 25 mg/m 2 of intravenous doxorubicin, 400 mg/m 2 of intravenous cyclophosphamide, and 1 mg of intravenous vincristine, on day 1 of each cycle; and 40 mg/m 2 of oral prednisone on days 1–5. Ofatumumab was administered with 1000 mg of paracetamol and 50 mg of diphenhydramine. The primary endpoint was overall survival in the intention-to-treat population. The statistical analysis has been done on an intention-to-treat principle. This study was registered withClinicalTrials.gov, numberNCT01195714 . Findings: Between June 2, 2010, and Nov 4, 2011, we enrolled 120 patients. Age-adjusted International Prognostic Index was 2–3 in 68 (57%) of them. The median follow-up time was 26·8 months (IQR 24·5–30·1). The 2-year overall survival was 64·7% (95% CI 55·3–72·7) and median overall survival was not reached (95% CI 30·2–not reached). 45 patients died during the treatment, of whom 28 (62%) died due to lymphoma. The most common side-effect was haematological toxicity. Among the 120 patients, grade 3–4 neutropenia was reported in 24 (21%) patients and thrombocytopenia in two (2%), during the treatment period. Grade 3–4 anaemia was reported in six (5%) patients; seven (6%) patients had one episode of febrile neutropenia. 17 (15%) of 115 patients in the modified intention-to-treat population had red blood cell transfusions and three (3%) had platelet transfusions. Interpretation: Our result suggest that, in patients older than 80 years with DLBCL, ofatumumab and pre-phase treatment seem to improve overall survival compared with the previously reported data. The combination of pre-phase treatment, a monoclonal antibody against CD20, and miniCHOP can be considered a new treatment platform for use in randomised clinical trial design for DLBCL treatment in patients older than 80 years. Funding: The Lymphoma Study Association, GlaxoSmithKline.